Die Erneuerung der politischen Mitte Das Auseinanderbrechen der Gesellschaft, das Format Volkspartei und die Zukunft der Demokratie - Benedikter, Roland (Nomos Verlagsgesellschaft mbH & Co. KG, 2022)
This book discusses the renewability of the political centre in European democracies. The recent environment of repeated bundles of crises, new social technologies, individualisation and the rise of populism has caused socio-psychological upheaval. As a consequence, the centre of open societies-the moderate middle ground-has been thinned out at the ballot box. This has led to the question: How might the political centre of liberal democracies be revived to preserve and further develop 'democracy within democracy' as the benchmark of dialogic moderation, community building, balance and reason? Has the traditionally designated format of the 'catch-all party' come to an end or does it have a future? Which models are available?